Bio‐Theoacoustics: Prayer Outdoors and the Reality of the Natural World. (December 2013) - Dahill, Lisa E.
Abstract What does it mean to pray when the Earth—the fabric of our bodies' lives, and indeed of the incarnation itself—is profoundly endangered from human action? What would Christian prayer look like that was not "losing track of nature" but following its tracks, physically and spiritually immersed in the actual, present, threatened and wild life of the more‐than‐human world? Using categories outlined by Dietrich Bonhoeffer in his Ethics, this essay asserts that prayer and worship that take place entirely within the wall‐, speech‐, and screen‐mediated bubble of anthropocentrism risk becoming an abstraction. The essay explores this assertion in three moves: first, it delineates Bonhoeffer's assertion of the "abstraction" created by forms of Christian life in which God is conceived in separation from the world. Next, it shows how these categories—"God" and "world"—come together in prayer outdoors, understood both literally and metaphorically. And finally, it proposes how prayer outdoors might take shape for individuals or communities: a bio‐theoacoustics of prayer for the life of the world.